The use of result-linking adverbials in argumentative essays by Indonesian EFL students - Pangestuti, Dina Agil; Ni Gusti Ayu Roselani (JEES (Journal of English Educators Society), 2025)
Understanding the use of result-linking adverbials in writing argumentative essays is crucial for both educators and EFL learners. However, EFL learners often struggle with the appropriate usage. Limited research has examined how Indonesian EFL learners employ these linking adverbials in argumentative writing. This study investigates the frequency, positional distribution, and functional usage of result - linking adverbials in argumentative essays written by Indonesian EFL Learners. It adopts a qualitative descriptive approach, analyzing 50 essays (each 200 -300 words) from the ICNALE corpus, authored by Indonesian EFL students at the B1_1, B1_2, and B2 proficiency levels. The essays address two standardized topics: part- time job for college students and smoking bans in restaurants. The data were analyzed with respect to result - linking adverbial types (so, therefore, hence, thus, consequently, and as a result), frequency, syntactic position (initial, medial, and final), and functional roles (e.g., concluding and cause - and - effect relationships). The findings revealed a predominance of “so” primarily in sentence - initial position, indicating overreliance on the informal register. Most result - linking adverbials were placed in the sentence - initial position, whereas “thus” was predominantly found in the sentence - medial position. Indonesian EFL students tended to use result - linking adverbial to draw conclusions rather than to indicate consequences or express cause - and - effect relationships. Habit formation, first language interference, and instructional practices are identified as potential factors affecting their usage of result-linking adverbials in argumentative writing. The results underscore the needfor targeted pedagogy that emphasizes register-appropriate use of linking adverbialand provides explicit instruction on their syntactic positioning.HIGHLIGTHS: The findings revealed a predominance of “So” primarily in sentence-initial position,indicating overreliance on the informal register. Most result-linking adverbials were placed in the sentence-initial position. Indonesian EFL students tended to use result-linking adverbial to draw conclusionsrather than to indicate consequences or express cause-and-effect relationships.